ENHANCING THE ROLE OF THE INVESTMENT CLIMATE IN ATTRACTING FOREIGN DIRECT INVESTMENT (Global Conference on Medical and Health Sciences, 2026)
In the modern global economy, foreign direct investment (FDI) is recognized as one of the most important factors accelerating economic growth, ensuring technological renewal, and increasing production efficiency. TTSI provides not only the flow of financial resources, but also serves the integration of advanced technologies, modern management practices, international marketing networks and innovative approaches into the national economy. Therefore, attracting TSA is one of the strategic priorities for any country.